Metaphors of adolescence during COVID-19 pandemic: a mixed-method analysis in relation to well-being and alexithymia - Farina, Eleonora; Pepe, Alessandro (Frontiers in Psychology, 2024)
This study investigates the association between alexithymic traits, self-perceived well-being, and self-representations in adolescents as expressed via narrative metaphors during the COVID-19 epidemic. The sample comprised 229 Italian adolescents (51.1% females, mean age=16.64). The research design was based on an exploratory, parallel, mixed-method approach. A semi-structured online interview was used as the major data gathering tool including both standardized quantitative questionnaire and open-ended questions. Data were analyzed by means of descriptive statistics, quantitative textual analysis and multidimensional co-word correspondence analysis. Main findings reveal a general low level of perceived well-being associated with alexithymia, affecting adolescents' lexical choices for their metaphors. Alexithymia-related low levels of well-being correspond to metaphors in which confusion and overpowering emotions predominate. Vivid pictures indicating vitality and a bright view on the future is often correlated with high levels of well-being. Metaphors emerge as powerful tools for investigating well-being in adolescents since closely related to inner states.